Efficient spatially resolved multimode quantum memory - Surmacz, K; Nunn, J; Reim, K; Lee, K; Lorenz, V; Sussman, B; Walmsley, I; Jaksch, D (2008)
Light storage in atomic ensembles has been implemented successfully, but the retrieval efficiency can be low. We propose to improve this efficiency with appropriately phase-matched backward propagating retrieval. This method allows for easy spatial filtering of the retrieved light; in addition, multiple optical modes can be stored in the transverse momentum of the ensemble. We model walk-off effects with a full numerical simulation, and confirm the applicability of the scheme. © 2008 The American Physical Society.